2023
DOI: 10.3390/ani13193035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artificial Light at Night on Fitness-Related Traits of Sea Urchin (Heliocidaris crassispina)

Xiuwen Xu,
Zexianghua Wang,
Xiuqi Jin
et al.

Abstract: Limited data are available regarding the effects of elevated coastal artificial light at night (ALAN) on intertidal echinoderms. In this study, we investigated the behavioral, morphological, and physiological responses of the sea urchin (Heliocidaris crassispina) after continuous exposure to ALAN at light intensities of 0.1, 300, and 600 Lux for 6 weeks. Our findings revealed that ALAN at 300 Lux substantially reduced food consumption, Lantern weight, and gonadosomatic index (GSI). On the other hand, ALAN at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(100 reference statements)
0
1
1
Order By: Relevance
“…Although we did not find interactive effects of ALAN and warming on grazing rates, urchins exposed to ALAN and fed fresh kelp had higher grazing rates compared to those exposed to normal day/night cycles. This was contrary to our predictions, and contrasts with previous studies that found no impact of ALAN on grazing rates for the urchins Arbacia lixula and Paracentrotus lividus [36], and a reduction in grazing rate of Heliocidaris crassispina with ALAN [37]. However, responses to ALAN can be highly species specific due to differences in biology and ecology, so this difference in response may reflect differences in photosensitivity and behaviour between species.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although we did not find interactive effects of ALAN and warming on grazing rates, urchins exposed to ALAN and fed fresh kelp had higher grazing rates compared to those exposed to normal day/night cycles. This was contrary to our predictions, and contrasts with previous studies that found no impact of ALAN on grazing rates for the urchins Arbacia lixula and Paracentrotus lividus [36], and a reduction in grazing rate of Heliocidaris crassispina with ALAN [37]. However, responses to ALAN can be highly species specific due to differences in biology and ecology, so this difference in response may reflect differences in photosensitivity and behaviour between species.…”
Section: Discussioncontrasting
confidence: 99%
“…The remaining tanks (n = 28) were assigned to 'ALAN' treatments, with a light cycle of 10 h light during the day (1500 lux, as per control treatment) and 14 h of dim light during the night (50 lux, measured at the surface of the water). This light intensity is within the range used by other studies looking at the effects of ALAN on urchins (30 lux [36]; 300 lux [37]). While the lux used here is brighter than ALAN levels measured on some intertidal shores in Sydney Harbour [60], it is within relevant levels of light that can occur directly under infrastructure such as ports and marinas [13].…”
Section: (B) Light and Temperature Treatmentsmentioning
confidence: 61%